INFLUENCE OF FAIRNESS AND EQUITY ON THE IMPLEMENTATION OF CONSTITUENCY DEVELOPMENT FUND PROJECTS IN NYERI TOWN CONSTITUENCY - Ndanyu, Joan; Kiarie, Dr. David; Nyaboke, Dr. Pamela (Journal of Public Policy and Administration, 2018)
Purpose: the purpose of this study was to determine the influence of the fairness and equity on the implementation of constituency development fund projects in Nyeri Town Constituency. Methodology: This research used descriptive survey research design. The population of target was 90 project management committee members from both primary and secondary schools that have benefited from Constituency Development Fund, and fourteen (14) sub chiefs whose areas have benefited from these projects. Collection of data was done by use of interview as well as questionnaires schedules. The analysis of the collected data was done by use of statistical package for social sciences (SPSS) to produce descriptive and inferential statistics. So as to test the extent of relationship amongst the variables a statistical confidence level of 95% was used. Results: The study found that fairness and equity had positive and significant effect on implementation of constituency development fund projects with Î² = 0.257 at p value 0.001. Unique contribution to theory, practice and policy: It was recommended that there should be clear channels provided to seek justice in case of unfair treatment in tendering process. Keywords: Fairness, equity, cdf, procurement